Sistem Informasi Rekrutmen Karyawan Baru pada PT Karya Putra Sapta Manunggal Berbasis Web - Lia Fajarwati; Rachmat Hidayat; Yusnia Budiarti (Program Studi Teknik Informatika Universitas Pamulang, 2020)
PT Karya Putra Sapta Manunggal is a company in the field of construction services based in Bekasi. In recruiting employees, PT Karya Putra Sapta Manunggal still uses conventional methods, namely that prospective employees usually send application files to the head office in Bekasi either by e-mail, post or by submitting applications directly to the Admin section. HRDs need to open e-mails and application files one by one which makes HRDs have to process applicants' data again, resulting in a high probability of errors. Therefore, it is necessary to create a new and effective system in order to facilitate the recruitment of employees using a system development methodology, namely the waterfall method. With the PHP programming language, codeigniter framework and mysql database, the employee recruitment website makes it easier for HRD to minimize time, costs and energy so that the recruitment process becomes more efficient. In addition, delivering clear and up-to-date information will improve the company's image.